Impact of the university degree subject and teaching faculty on the language learning strategies of students - M. Cristina, Santana-Quintana (Revista de Estilos de Aprendizaje, 2021)
This paper questions whether university students use Language Learning Strategies (LLS) and if there is a possible relationship between LLS and the variables ‘university degree subject’ and ‘teaching faculty’. According to the results of the Strategy Inventory for Language Learning, the students of the disciplines analyzed presented a moderate use of LLS. Their preference for some strategies over others depends on the subject of their university degree. The results obtained from the variables also suggest that there may be a relationship between the teaching faculty and the student’s choice of LLS. This study obtains more empirical evidence of the conditions that allow students to make the most of education to develop competences in learning a foreign language as well as to emphasize that teachers must employ appropriate measures.